Transformation of Generation Z Work Motivation through Information Transparency, Performance Recognition, and Technology Support in Palembang Telecommunication Industry in Indonesia - Maiza Fikri; Yenik Pujowati; Agus Setiyawan (West Science Interdisciplinary Studies, 2024)
This study explores the influence of information transparency, performance recognition, and technology support on the work motivation of Generation Z employees in the telecommunication industry in Palembang, Indonesia. Using a quantitative approach, data were collected from 48 respondents through a structured questionnaire with a Likert scale of 1 to 5 and analyzed using SPSS version 26. The findings indicate that all three factors significantly and positively impact work motivation, with technology support emerging as the strongest predictor. The results highlight the importance of fostering transparent communication, implementing effective recognition systems, and providing advanced technological tools to engage and motivate Generation Z employees. These insights offer valuable implications for human resource strategies in the telecommunication sector.